2010
DOI: 10.15282/ijame.2.2010.4.0012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygenated Hydrocarbon Additives on Exhaust Emission of a Diesel Engine

Abstract: The use of oxygenated fuels seems to be a promising solution for reducing particulate emissions in existing and future diesel motor vehicles. In this work, the influence of the addition of oxygenated hydrocarbons to diesel fuels on performance and emission parameters of a diesel engine is experimentally studied. 3-Pentanone (C 5 H 10 O) and Methyl anon (C 7 H 12 O) were used as oxygenated fuel additives. It was found that the addition of oxygenated hydrocarbons reduced the production of soot precursors with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Furthermore, biodiesel offers compensations regarding engine wear, cost and availability [14,15]. Pollutants produced are less harmful comparatively [16,17]. Biodiesel has low sulphur content, low aromatic content and oxygen containing compounds due to which the emissions of SO2, CO2, HC and PM are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biodiesel offers compensations regarding engine wear, cost and availability [14,15]. Pollutants produced are less harmful comparatively [16,17]. Biodiesel has low sulphur content, low aromatic content and oxygen containing compounds due to which the emissions of SO2, CO2, HC and PM are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the hydrophobic nature of CNTs, which have higher tendency to agglomerate in conventional fluids [23][24][25][26][27][28]. Stability is the main factor that contributes to thermo-physical performance [29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effects of injection timing on engine performance for biodiesel [17][18][19][20][21]. Carraretto, Macor [22] observed that power and torque were increased up to almost pure diesel levels by reducing injection advance.…”
Section: Introductionmentioning
confidence: 99%